Marxism and the oppression of women : toward a unitary theory - Vogel, Lise (Historical materialism book series, 2013)
Marxism and the Oppression of Women opens up an original direction in the Marxist-feminist theorisation of gender and capitalist reproduction. This edition elaborates Lise Vogel's unique contribution via a new introduction and Vogel's 2000 article "Domestic Labor Revisited."